322 Evaluation of the biological function of genes linked to regions with distortion of Mendelian segregation and their relation to reproductive traits in dairy cattle. (7th December 2018) - Suárez-Vega, A; Miglior, F; Id-Lahoucine, S; Casellas, J; Fonseca, P; Sargolzaei, M; Miller, S; Schenkel, F; Medrano, J; Cánovas, A
Abstract: Distortion of the Mendelian segregation or transmission ratio distortion (TRD) refers to the significant departure from Mendel's law of the transmission of alleles from heterozygous parents to offspring. This phenomenon has been attributed to various biological mechanisms before fertilization, during fetal and embryonic development and in neonatal life. Thus, TRD has been associated with impaired fertility and offspring survival at embryonic, fetal and postnatal stages. The objective of this study was to evaluate the functional consequences of genomic regions showing TRD in a population of 436, 651 Holstein dairy cattle with trios of raw genotypes. Genotype data (trios) included genotypes from dam, sire and offspring using medium and high density SNP arrays. Functional analysis included 877 positional genes associated with all SNPs previously identified as displaying strong significant TRD (Bayes Factor ≥10), using a Bayesian approach. Gene ontology (GO) and network analyses were performed using WebGestalt and STRING software. The GO analysis showed significant biological processes related to embryonic stages, such as regulation of mitotic cell cycle, stem cell population maintenance, skeletal system morphogenesis or forebrain development. In addition, the genes within significant TRD regions were further investigated performing gene networks analysis. A total of 849 specific and meaningful connections between the genes were detected (p-value< 1.0e-16), meaning that there were more associations between genes related to TRD than the ones that could be expected by chance. The highest enriched metabolic pathway in the gene network was the regulation of actin cytoskeleton. This pathway has been linked to sprouting of neurites in early embryonic differentiation. Hence, functional analyses on TRD regions showed that the positional candidate genes might have a direct impact on embryo development. Additional data mining approaches will be performed to identify key regulator genes, which may harbor potential structural variations that directly affect reproductive traits in dairy cattle.